ESTIMATION OF CHARACTERISTICS FOR CRACK RESISTANCE OF METAL PIPELINES DURING CONTINUOUS OPERATION - Грабовський, Роман Степанович; Барна, Роман Андрійович; Мазур, Мирослав Павлович; Федорович, Ігор Ярославович; Лепак, Олег Миронович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
During continuous operation of steels of major pipelines characteristics of resistance for cracks spreading in the air and corrosive medium (pH 6,7) NS4 have been estimated that was used as a model of ground water. The influence of rolling direction on the spreading velocity of fatigue cracks has been researched. Parameters of the thermal influence zone of the researched section of the gas pipeline have been measured experimentally. The rate of fatigue cracks development has been studied in the metal of the gas pipeline and basic metals of the thermal influence zone of the weld seam as well.